PRODUKSI BAKTERI ASAM LAKTAT (BAL) KANDIDAT PROBIOTIK DARI FERMENTASI AIR CUCIAN BERAS DAN SUSU - Sofian Soib; Indah Anggraini Yusanti; Neny Rochyani (Jurnal Sains dan Teknologi Pangan, 2023)
This study aims to determine lactic acid bacteria (LAB) isolates from fermented rice water and milk, to determine the characteristics of the LAB isolates obtained. LAB isolation was carried out using a multilevel dilution technique using peptone water  diluent solution 1%. Samples were diluted to 10-7 then grown on MRS Agar media added with 1% CaCO3 and incubated at 37˚C for 48 hours. The characterization of LAB isolates was carried out following the rules of Bergey's Manual of Determinative Bacteriology, namely based on morphological, physiological and biochemical characteristics. The results showed that there were three bacterial isolates namely A1 (Bacillus sp), A2 (Staphylococcus sp) and A3 (Aerococcus sp) which had the potential as probiotic candidates. Characteristics of probiotic candidate bacterial isolates: gram positive and catalase positive for all bacterial isolates, then motile, oxidase positive and fermentative for isolate A1, while non motile, oxidase negative and oxidative for isolates A2 and A3